Assistência pré-natal e puerpério no âmbito da atenção básica no Brasil - SOUSA, Dimauro Soares de (Universidade Federal do Pará, 2025)
Recognizing Primary Care as the preferential gateway to public health services and its role in organizing care, investigating prenatal and puerperal care is essential for measuring its reach and quality, in order to provide subsidies for making decisions based on the results. Objectives: To analyze prenatal and postpartum care within the scope of Primary Care in Brazil. Methodology: This is a research with a quantitative and analytical approach. Brazil is the reference for this study. The variables related to the External Evaluation of the third cycle of the National Program for Improving Access and Quality of Primary Care were used for the research, Module II – Interview with the professional, coordinated by the ministry of health, from 2017 to 2018, which includes interviews with key informants. Teams were categorized by federative units and geographic regions, and data analysis were done using descriptve statistics, using absolute and relative frequency. All analyzes were done in IBM SPSS Statistics Software, version 20.0, and presented in the form of charts, graphs and figures. Results: The collection of data for the External Assessment that make up the second phase of the third cycle of the National Program for Improving Access and Quality in Primary Care, had the adhesion of 5.324 cities (95,6%). A total of 38,865 primary care teams in Brazil were evaluated, of these 36.702 (98,30%) teams perform prenatal consultations, 35.771(97,50%) presente a document proving the prenatal consultation, 36.433 (99,3%) of the primary care teams use the pregant woman’s handbook to monitor the pregnat women and 34.096(92,90) of those teams have a copymirror of the pregnant women’s handbook, or another form with equivalent information, at the Basic Health Unit. Regarding to the actions carried out by the team to guarantee the postpartum consultation up to one week after the childbirth, all of the brazilian regions have low rates of consultation at special times, in which any day of the week, with 65.4% adherence in this aspect. Conclusion: The results suggest that there are differences in prenatal and puerperal care in Brazilian regions. These results can be useful for other studies and for strengthening reginal planning actions. For managerial practice, the assistance during the prenatal and postpartum period must be repeatedly discussed.